Relationship Between Work Engagement, Psychosocial Risks, and Mental Health Among Spanish Nurses: A Cross-Sectional Study - García-Iglesias, Juan Jesús; Gómez-Salgado, Juan; Ortega-Moreno, Mónica; Navarro-Abal, Yolanda (Frontiers in Public Health, 2021)
Background: Exposure to risk factors may lead to health problems of varied nature and to an increased risk of suffering accidents at work. Objectives: The aim of this study was to evaluate the work engagement, psychosocial risks, and psychological well-being of Spanish nurses, analysing existing relationships and their associations with self -reported mental health problems of nurses. Methods: To this end, a cross-sectional observational study was carried out with a sample of 1704 Spanish nurses between January 2019 and January 2020, using a self-administered questionnaire containing sociodemographic variables, the Spanish version of the Copenhagen Psychosocial Questionnaire (CoPsoQ-istas21), the Utrecht Work Engagement Scale (UWES-9), and the General Health Questionnaire (GHQ-12). Results: The Kruskal-Wallis test showed that nurse perceptions for each of the tests differed significantly among different healthcare areas (p < 0.05). The results indicated that emergency nurses offered higher scores in all dimensions of the CoPsoQ-istas21 and GHQ-12 tests; and in primary care, nurses scored higher in all three dimensions of the UWES-9 test. In addition, self-perceived health and vigour at work were identified as predictive factors of mental health. Conclusions: A high percentage of Spanish nurses perceived a high level of psychosocial risk in the exercise of their duties and nearly 41% could suffer from some mental health-related problem. Primary Care nurses showed higher levels of work engagement and lower perception of psychosocial risks than Emergency nurses. Results may allow to identify a professional profile which is more likely to suffer from psychological distress, as both the working conditions and the work commitment expressed by nurses in their daily work are key elements in assessing the possible psychosocial risks to which they may be exposed.